A Sum of Its Parts: Party Fit and Party Change in the U.S. House. Issue 5 (September 2021) - Lee, Daniel J.; Goff, Sean M.
Previous research has noted the transformation of the American parties since the 1970s, as exhibited in their increased ideological polarization and transformation on social issues like civil rights, abortion, and the environment. We contribute to the literature on party change by theoretically stressing the decentralized and individualistic nature of American parties, while using a measure of party change that is based on legislative behavior beyond roll call voting. Our paper uses social network analysis to analyze the parties from the 93rd to 110th Congresses, utilizing bill cosponsorship to define connections between members. Our analysis illustrates how the core of the party, that is, who are most central in the cosponsorship network, has changed over time. We find evidence that party centrality influenced retirement decisions, thereby reinforcing and contributing to party change.